Definition, Klassifikation, klinische Diagnose und Prognose des Fibromyalgiesyndroms: aktualisierte Leitlinie 2017 und Übersicht von systematischen Übersichtsarbeiten = Definition, classification, clinical diagnosis and prognosis of fibromyalgia syndrome : updated guidelines 2017 and overview of systematic review articles - Eich, Wolfgang (Der Schmerz, 2017)
BackgroundThe regular update of the guidelines on fibromyalgia syndrome, AWMF number 145/004, was scheduled for April 2017.MethodsThe guidelines were developed by 13 scientific societies and 2 patient self-help organizations coordinated by the German Pain Society. Working groups (n =8) with a total of 42 members were formed balanced with respect to gender, medical expertise, position in the medical or scientific hierarchy and potential conflicts of interest. A systematic search of the literature from December 2010 to May 2016 was performed in the Cochrane library, MEDLINE, PsycINFO and Scopus databases. Levels of evidence were assigned according to the classification system of the Oxford Centre for Evidence-Based Medicine version 2009. The strength of recommendations was achieved by multiple step formalized procedures to reach a consensus. The guidelines were reviewed and approved by the board of directors of the societies engaged in the development of the guidelines.Results and conclusionThe clinical diagnosis of fibromyalgia syndrome can be established by the American College of Rheumatology (ACR) 1990 classification criteria (with examination of tender points) or without the examination of tender points by the modified preliminary diagnostic ACR 2010 or 2011 criteria.
Paralleltitel von Frontdoor übernommen
Gesehen am 29.11.2018